2016
DOI: 10.1002/eej.22871
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dislocation Structures in 4H‐SiC by Synchrotron X‐Ray Topography

Abstract: SUMMARY Current 4H‐SiC wafers contain certain amount of dislocations, stacking faults, and other lattice‐defects. These defect structures evolve during various processes for power device fabrication. It is very important to examine evolutions of dislocation structures during power device processes, as well as the effect of dislocations on performances of fabricated power devices. Since lattice defects can be observed at only subsurface regions selectively by Berg–Barrett X‐ray topography, we have applied this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…Additionally, it helps to understand the extremely small activation energy for the REDG in 4H-SiC because in this case to enhance the dislocation glide the kink formation energy should be only lowered. If the activation energy for the kink migration is indeed very low, this allows a fresh look on the results obtained previously [13,14], which showed that SSFs introduced under a mechanical shear stress at elevated temperatures did not expand due to subsequent LEEBI despite the fact that the expansion of SSFs under irradiation and under mechanical shear stress was driven by the similar dislocations, namely Si-core 30 • PDs [22][23][24]. If one takes into account that, as theory predicted [46,47], the barrier for the kink migration can be of about 30-60 meV for some core configurations (e.g.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Additionally, it helps to understand the extremely small activation energy for the REDG in 4H-SiC because in this case to enhance the dislocation glide the kink formation energy should be only lowered. If the activation energy for the kink migration is indeed very low, this allows a fresh look on the results obtained previously [13,14], which showed that SSFs introduced under a mechanical shear stress at elevated temperatures did not expand due to subsequent LEEBI despite the fact that the expansion of SSFs under irradiation and under mechanical shear stress was driven by the similar dislocations, namely Si-core 30 • PDs [22][23][24]. If one takes into account that, as theory predicted [46,47], the barrier for the kink migration can be of about 30-60 meV for some core configurations (e.g.…”
Section: Discussionmentioning
confidence: 81%
“…It has been well established that SSFs can be introduced at room temperature in power devices at high forward currents [3-8, 18, 21] or under electron beam or optical irradiation [10][11][12][13][14][15][16][17]. As the SSF expansion in 4H-SiC under mechanical shear stress was observed only at temperatures exceeding 250 • C [13], their expansion at room temperature suggests a strong effect of excess carriers on the mobility of partial dislocations (PDs) driving the SSF expansion (Si-core 30 • PDs [22][23][24]). For the dislocation glide in semiconducting covalent crystals an intrinsic potential barrier, the so-called Peierls potential, should be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…Метод Берга-Барретта успешно был использован для изучения структурных дефектов в различных кристаллах, например, взаимодействия дислокаций в цинке [38], оценке качества сильнопоглощающих кристаллов [39,40], исследования дефектов в многослойных эпитаксиальных силовых приборах на основе кремния [41]. Рентгеновская монохроматическая топография Берга−Барретта с использованием синхротронного излучения (СИ) явилась эффективным методом исследования дислокаций и дефектов упаковки в силовых устройствах на основе карбида кремния и их влияния на производительность этих устройств [42,43].…”
Section: метод берга−барреттаunclassified
“…It has been well established that SSFs can be introduced at room temperature in power devices at high forward currents [3][4][5][6][7][8]19,22] or under electron beam or optical irradiation. [10][11][12][13][14][15][16][17] As the SSF expansion in 4H-SiC under mechanical shear stress was observed only at temperatures exceeding 250 °C, [13,18] their expansion at room temperature suggests a strong effect of excess carriers on the mobility of partial dislocations (PDs) driving the SSF expansion (Si-core 30°PDs [23][24][25] ). For the dislocation glide in semiconducting covalent crystals an intrinsic potential barrier, the so-called Peierls potential, should be overcome.…”
Section: Introductionmentioning
confidence: 99%